Effectiveness of different edutainment interventions -“Poem &Gestures, Video Show and Peer Demonstration”- for proper hand washing: A comparative pilot study among selected Myanmar preschoolers - Swe, Swe Latt; Tin, Myo Han; Nwe , Nwe Oo; Than , Than Myint; Htun , Lynn Aung; Hlaing , Hlaing Hlaing (2015)
Background: Edutainment using songs, poem with gesture, finger puppet shows, video shows, games and demonstration method with audiovisual aids are mostly applied in health education activities for preschoolers. In the study, effectiveness of different edutainment interventions to acquire proper hand washing (PHW) knowledge and practices among Myanmar preschoolers was compared to assist in setting further health education plan for PHW which is the single most effective way to prevent the spread of infections transmitted by contaminated hands. Methods: A Quasi-experimental study was conducted at No-1, pre-primary school in Mandalay, Myanmar in 2006 to compare the effectiveness of three different edutainment interventions (poem & gesture, video show and peer demonstration) in which knowledge (why to wash, when to wash) and practices (how to wash) for PHW were included based on WHO guide lines. Sixty preschoolers aged within 3-5 years and similar socio-demographic status was selected to form 3 groups (A, B and C) with 20 in each. Participatory style teaching–learning using poem & gesture in Group-A and 10 minutes video show in Group-B were intervened. Five peers were selected from Group-C and trained them for peer demonstration for PHW in their group. The knowledge of PHW was assessed using pre-structured questionnaires in face to face interview with the preschoolers and their practice was assessed by the checklist before and one month after the intervention. Results: The total knowledge and practices scores of the preschoolers on PHW were significantly (p <0.05) increased in all three groups after one month edutainment interventions. The highest mean score differences (in percent) before and after the intervention was noticed in Group-C (49.3±12), comparing with Group-A (47±17.6) and Group-B (33.3±17.6). In accordance with Scheffe post-hoc test comparison, significant (<p<0.05) mean score differences was found between Group-A and Group B with 4.1 % and between Group-C and Group-B with 4.7%. There was no significant mean scores differences (p>0.05) between Group-A and Group-C with 0.7%. Conclusion: The comparison results highlighted that peer demonstration (Group-C) and poem & gesture (Group-A) may be the most effective edutainment interventions for the Myanmar preschoolers to acquire proper hand washing knowledge and practices.